Simulation on Water Diversion Regulation Effect in the Central Ditch of Hengqin New District,Zhuhai - LONG Xiaofei; WU Yaju; FAN Qunfang; ZHU Song; WANG Hua; ZHU Jinhe (Renmin Zhujiang)
The tidal river network area of the Pearl River Delta uses the ebb-and-flow differences between tidal level of the outer river and water level of the inland river to divert clear water for regulation.This is an effective way to improve the water environment of the tidal river network.The central ditch of Hengqin New District is in the tidal river network area of the Pearl River Delta.To improve the water environment of the central ditch in Hengqin New District,this study builds a one-dimensional hydrodynamic mathematical model of water quality and investigates the hydrodynamic regulation scheme for improving the regional water environment.Then,the water exchange effects of the original regulation scheme and the optimized regulation scheme are calculated and analyzed.The simulation results show that the optimized regulation scheme increases the regional flow rate by 0.20 m/s,shortens the half-exchange period by 101.5 h,and increases the water exchange rate by a factor of 1.1,which demonstrates a great improvement effect on the regional water environment.The results can be used as a reference for the implementation of the water diversion regulation scheme in the tidal river network area.